Intimate Partner Violence and Depression of Mothers and Their Adolescent Children: The Roles of Housing Insecurity and System Contacts - Marçal, Katherine E. (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) victimization is a prominent risk factor for depression among mothers. Less is known about the long-term relationship between IPV and maternal depression, impacts of IPV exposure on children, and mechanisms linking IPV with long-term mental health problems. IPV threatens stable housing for survivors, which increases likelihood of surveillance and sanctioning by formal systems ? in particular, child welfare and criminal justice. The present study investigates whether housing insecurity and system contacts mediate the relationship between maternal IPV victimization and depression among both mothers and children 10 years later. Data comes from the Fragile Families and Child Well-being Study, a longitudinal survey of at-risk families with children. Structural equation modeling investigates pathways from IPV victimization of mothers to maternal and child depression via housing insecurity and contact with the child welfare and criminal justice systems. Results show IPV victimization is directly associated with housing insecurity, child welfare contact, and adolescent depression. Further, housing insecurity leading to both types of system contact mediates the link from IPV to maternal depression; in contrast, housing insecurity alone mediates the link from IPV to depression among children when they are 15 years old. Findings suggest IPV toward mothers has enduring, multigenerational effects on mental health that unfold over a long period following victimization. Complex pathways suggest housing insecurity and contact with punitive social systems that disproportionately impact low-income families explain in part the link from IPV to depression. Lack of housing options may deter survivors from leaving violent relationships, and housing insecurity in the wake of victimization may contribute to interactions with punitive social systems. Efforts to address housing, stigma, and psychological needs of IPV survivors are crucial to stabilize families.